APPLICATION EXPERIENCE OF PROCALCYTONINE TEST FOR THE DIFFERENTIAL DIAGNOSTICS OF THE ACUTE SYSTEMIC INFLAMMATORY RESPONSE - S.I. Valieva; E.I. Alexeeva; T.M. Bzarova; A.M. Chomakhidze; K.B. Isaeva ("Paediatrician" Publishers LLC, 2007)
The article provides the clinical observation, allowing for the conclusion that the use of pct test in the daily practice of a rheumatologist makes it possible to early carry out differential diagnostics of a patient with the manifestations of the systemic inflammatory response and to duly start necessary pathogenetic and/or etiotropic therapy. Key words: procalcytonine test, sepsis like syndrome, treatment, children.